THE EFFECT OF CONFLICT TO THE PEACEFUL COEXISTENCE OF THE SOCIETIES - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
It is a concept synonymous with human behaviours. Since man cannot exist in isolation, then in the course of interactions with other members of the community there will be disagreements, intrigues and misunderstanding. The disagreement or misunderstanding occurs in forms of revolution or war. The reasons for the conflict may be as a result of cheating or struggle for a beneficial goal. To make peace and/or put an end to the conflicts, various measures are adopted by both parties and intervening parties to reach an agreement or compromise. In understanding the meaning of conflict, it must be seen from the perspective of inter-group relations whether, as individuals or groups.